Mapping the RNA methylome under drought: techniques, mechanisms, and agricultural implications - Fan, Xiaoru; Zhang, Yong (Frontiers in Plant Science, 2026)
Drought stress is one of the most devastating threats to global agriculture. Understanding plant adaptation to water scarcity is of paramount importance for food security. In the last several years, epigenetic regulation, especially RNA methylation, has been shown to play an important role in post-transcriptional gene regulation in plant stress response. Here, we summarize recent advances in studying the epitranscriptomic mechanisms underlying plant drought tolerance. We will introduce various types of RNA modifications, provide an overview of “writer”, “eraser” and “reader” proteins mediating m6A modification in plant system, and discuss different technologies for detecting m6A and several other modifications including m5C, m1A, m3C, m7G and m1A with focus on principles and technical consideration. Finally, we will discuss evidence from multiple species to suggest that water deficiency can alter the abundance of m6A modification on RNA molecules in a dynamic manner. The modified transcripts go through differential stability, translation efficiency and process proficiency levels to regulate various physiological processes including but not limited to stomatal movement, ROS signaling and hormonal action. Furthermore, we will also highlight the possible means through which modulation of m6A level could be utilized for generating drought tolerant crops through genetic or biotechnological approaches. This analysis establishes RNA methylation, particularly m6A, as a pivotal and reversible regulatory mechanism in plant drought stress responses and identifies key future research avenues for both fundamental understanding and crop improvement.